Prevalence of Gastrointestinal Parasitic Infections in Pigs of North Eastern Region of India - LAHA, R.; DAS, M.; GOSWAMI, A.; SAILO, B.; SHARMA, B.K.; GANGMEI, D.; PUII, L.H.; PATRA, M.K.; DAS, R.K.; SHARMA, A.; NGULLIE, E. (Indian Journal of Hill Farming, 2015)
A total of 5511numbers of faecal samples of pigs were collected from four states of North Eastern (NE) Region of India namely Meghalaya, Manipur, Mizoram and Nagaland, for a period of two years, to know the prevalence of gastrointestinal parasitic infections in pigs in these four states. The examination of faecal samples of pigs revealed overall 37.77% pigs were infected with gastrointestinal parasitism with a distribution of 36.34%, 47.31%, 34.45% and 60.95% infections with mean faecal egg count in terms of eggs per gram of faeces (EPG) 1289.13, 2038.44, 475.19 and 897.26 in Meghalaya, Nagaland, Mizoram and Manipur, respectively. Amongst helminthes, over all, Ascaris suum infections (65.46%) were predominant in these four states followed by Strongyle spp. (45.96%), Strongyloides spp. (13.06%) and Trichuris spp. (16.66%). Amongst protozoa Eimeria spp.(34.00%) was recorded in all these four states and Isospora spp.(3.50%) was recorded in three states, except Meghalaya. Individually, the pigs of Manipur have been found to harbor higher percentage (52.34%) of infection with Isospora spp. The present study indicates Ascaris suum as the most prevalent helminthes in pigs in these four NE states and also indicates lowest percentage of infections with lowest EPG in Mizoram and highest percentage of infections in Manipur. Highest percentage of infection does not indicate highest EPG.